THE CORRELATION OF LIFESTYLE WITH HYPERTENSION IN ADULTS IN RT 03 RW 01 DUKUH KARYA VILLAGE - Dina, Neng; Hilda Meriyandah Agil; Dinda Nur Fajri Hidayati Bunga (Rena Cipta Mandiri, 2025)
High blood pressure or hypertension is a state of increased blood pressure, both systolic and diastolic, which is more than 140/90 mmHg. Lifestyle is the most important factor that greatly affects society. An unhealthy lifestyle can cause hypertension / high blood pressure. Many risk factors that can increase the occurrence of hypertension include diet, physical activity, rest habits, smoking habits. In this study, there were 115 respondents aged 21-40 years and dominated by women who found that their blood pressure was above normal. Research Objectives : This study aims to determine the relationship between the relationship between lifestyle with the incidence of hypertension in adults in RT 03 RW 01 Dukuh Karya Village. Research Methods : The research method used is quantitative with cross-sectional analytic research. The populatin in this study is the community of RT 03 RW 01 Dukuh Karya Village totaling 142 respondents. The data collection technique was using purposive sampling. Research Results : It was found that there was a significant relationship between diet (a value = 0,008), physical activity (a value = 0,016), rest habits (a value = 0,020), smoking habit (a value = 0,041) with the incidence of hypertension in adults in RT 03 RW 01 Dukuh Karya Village. Conclusion : There is a relationship between lifestyle and the incidence of hypertension in RT 03 RW 01 Dukuh Karya Village.